The era of resistance training as a primary form of physical activity for physical fitness and health in youth has come - Chaabene, H.; Ramirez-Campillo, R.; Moran, J.; Schega, L.; Prieske, O.; Sandau, I.; Negra, Y.; Behrens, M. (Sports Medicine, 2025)
Resistance training (RT) is widely regarded as the gold standard approach for enhancing muscular fitness (i.e., muscle strength, power, and muscular endurance) in youth while also providing health and physical fitness benefits traditionally associated with aerobic training (e.g., enhanced cardiorespiratory fitness, reduced body fat, improved insulin sensitivity). Additionally, while bone health can be improved following RT (particularly after plyometric jump training), aerobic training may result in a lesser or even neutral impact on bone mineral density enhancement (e.g., swimming). Regarding mental health and cognition, while aerobic training has well-established positive effects, preliminary evidence in obese youth suggests that RT may offer greater benefits in certain aspects compared to aerobic training. Additionally, RT can reduce the risk and incidence of injuries in youth. Overall, we argue in this Current Opinion article that the current consideration of RT as an additional, rather than essential (possibly even the most essential), aspect of physical activity in current national and international guidelines needs to be reconsidered. Overall, there is an urgent need to inform relevant stakeholders that, while aerobic activities remain essential, the next generation of physical activity guidelines should place greater emphasis on the particular importance of RT, providing more comprehensive guidance on its implementation for youth.